Two new combinations in Plagiobothrys (Boraginaceae subtribe Amsinckiinae) - Guilliams, C. Matt; Kelley, Ronald B. (Phytotaxa, 2025)
The genus Allocarya (Boraginaceae subtribe Amsinckiinae) was proposed by E.L. Greene in 1887 to unite 18 annual herbaceous taxa from North America and South America. Taxonomists greatly expanded the genus through the 1920s, although the more conservative taxonomic approach advocated by I.M. Johnston coupled with his transfer of Allocarya to the genus Plagiobothrys resulted in the relegation of many early Allocarya names to synonymy. While preparing the taxonomic treatment of genus Plagiobothrys for the Flora of North America project, we studied specimens that corresponded to two presently unrecognized Allocarya taxa, which on the basis of morphology and geographic distribution we find to be worthy of recognition. We briefly describe these two taxa and make the new combinations for them in Plagiobothrys.